GAMBARAN PENGETAHUAN, SIKAP DAN PERILAKU REMAJA PUTRI TENTANG ANEMIA DEFISIENSI BESI - dea pratiwi; Sunarti; Sitti NurDjannah (Avicenna: Jurnal Ilmiah, 2023)
Background: Iron deficiency anemia is the most common nutritional problem in adolescents worldwide, especially in developing countries, including Indonesia. Anemia caused by iron deficiency is very common in Indonesia among pregnant women, children under two years of age, school-age adolescents and low-wage workers and vulnerable groups. One reason is the lack of knowledge about the impact of anemia which can affect attitudes and behavior in dealing with anemia. The purpose of this study was to determine the level of knowledge, attitudes and behavior of adolescents towards iron deficiency anemia. Method: this study uses a quantitative approach that is descriptive in nature with cross-sectional. The sample in this study was taken using a random sampling method with a total of 30 young women. Data collection used a questionnaire in the form of a google form. Data management used Microsoft Excel. Results: more than half of the respondents had good knowledge, namely 63.33%, for a positive attitude, it was 53.33%, while for behavior, half of the respondents had unfavorable behavior of 53.33%. Conclusion: most teenagers still do not know the causes and effects of anemia, and the behavior of adolescents who are still lacking in preventing anemia can cause short-term effects such as decreased concentration in learning and learning achievement while the long-term impact can cause bleeding before and during giving birth, giving birth to stunting and LBW babies.